Challenges of Translating Figurative Language in ‘How Far I’ll Go’: Translatability vs. Untranslatability - Saragih, Rode Arta Yuliani; Ashadi, Ashadi; Triyono, Sulis (JOLLT Journal of Languages and Language Teaching, 2025)
Translatability and untranslatability have been significant issues in song translation, particularly regarding figurative expressions. The present study aims to investigate the translatability and untranslatability of figurative language found in the song lyric â€œHow Far Iâ€™ll Goâ€ and its translated version, â€œSebâ€™rapa Jauh Ku Melangkahâ€. It also examines the translation techniques employed by the translator to address these issues. This qualitative study was conducted in the light of Kennedyâ€™s (1979) classification of figurative language and the application of Molina & Albirâ€™s (2002) translation techniques.Â The finding of the study revealed two types of figurative language translation: translatability and untranslatability. Translatability was found in the translation of personification and hyperbole, while untranslatability was found in the translation of lyrics featuring alliteration, symbolism, and assonance. To address these translation challenges, the translator employs several techniques: particularization, amplification, and reduction were used to translate the personification and hyperbole.Â In contrast, amplification and particularization were applied to tackle the untranslatability present in alliteration, symbolism, and assonance. The untranslatability issue arises due to several factors: linguistic and cultural untranslatability, that can result in meanings from the source language being not equivalent or are unknown in the target language. To address untranslatability, the translator often needs to make creative decisions to capture the core meaning and message of the source text while considering the linguistics, cultural, and stylistic context of the target text. Song translation is a complex process that involves more than just the ability to transfer meaning, but also creativity and cultural sensitivity.